CNT-coated Ti < 3 > C < 2 > T < x > MXene coupled porous g-C3N4 photocatalyst as well as preparation method and application thereof

Porous g-C3N4 is prepared by one-step calcining method in the photocatalyst and coupled with CNT@Ti3C2Tx MXene through electrostatic self-assembly method, the problem of inefficiency of the photocatalyst is solved and efficient organic degradation effect is achieved.

CN119702045APending Publication Date: 2025-03-28TAICANG SIDIKE NEW MATERIALS SCI & TECH CO LTD +2
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202510087002.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Existing photocatalytic degradation of organic pollutants has problems with inefficiency, especially due to the poor electron transport performance of Ti3C2Tx MXene sheet self-stack and g-C3N4 bandgap wide.

Method used

Porous g-C3N4 was prepared by one-step calcination method, and the protonated porous g-C3N4 was coupled with CNT@Ti3C2Tx MXene nanosheets by electrostatic self-assembly to form a heterostructure, inhibiting the self-stacking of Ti3C2Tx MXene, and improving the photocatalytic response characteristics.

Benefits of technology

It achieves efficient degradation of organic matter under visible light conditions, improves the visible light catalytic effect of photocatalysts, and is environmentally friendly and safe in the preparation process, suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119702045A_ABST
    Figure CN119702045A_ABST
Patent Text Reader

Abstract

The invention discloses a CNT (at) Ti < 3 > C < 2 > T < x > MXene coupled porous g-C3N4 photocatalyst and a preparation method and application thereof. G-C3N4 is prepared through a one-step calcination method, and g-C3N4 which is good in dispersion and large in porosity is obtained through thermal stripping; and coupling the protonated porous g-C3N4 with a negatively charged CNT (at) Ti < 3 > C < 2 > T < x > MXene nanosheet through an electrostatic self-assembly method to form a heterostructure, so as to obtain the photocatalyst capable of efficiently degrading organic matters under a visible light illumination condition. An environment-friendly and safe pyrolysis method is adopted in the preparation process, operation is easy, the method is very suitable for large-scale production, and the method has good application prospects in the fields of sewage treatment, waste gas treatment and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of nanomaterials and photocatalytic degradation of organic pollutants, and in particular to a CNT@Ti3C2T x MXene-coupled porous g-C3N4 photocatalyst, its preparation method and application. Background Art

[0002] Since the 21st century, with the rapid progress of social civilization, the consumption of fossil fuels and water pollution have received widespread attention. They have caused energy shortages, environmental pollution and abnormal climate change, which are urgent problems that need to be solved for mankind. Rhodamine B (RhB) is the most typical organic pollutant, which is carcinogenic and difficult to degrade into non-toxic and harmless substances. Among many cutting-edge technologies, photocatalytic technology has attracted much attention due to its excellent cleanliness and huge application potential. Ordinary semiconductor photocatalysts have poor catalytic effects due to problems such as large band gaps. Doping with co-catalysts such as precious metals can improve this problem. However, the high cost and scarcity of precious metals limit their large-scale application. In recent years, a new type of two-dimensional layered material Ti3C2T x MXene has attracted wide attention in the field of photocatalysis due to its large specific surface area, excellent conductivity and abundant surface groups. x When MXene is used as a co-catalyst, its sheets are prone to self-stacking, which reduces the electron transport performance and limits the Ti3C2T x Application of MXene. Graphitic carbon nitride (g-C3N4) is a new type of semiconductor with broad application prospects in the field of photocatalysis. However, due to its wide band gap and fast recombination rate of photogenerated electrons and holes, its photocatalytic performance is not high. In order to improve the photocatalytic performance of g-C3N4, g-C3N4 was combined with Ti3C2T x MXene co-catalyst composite is an effective way to improve its photocatalytic efficiency.

[0003] Due to the wide band gap of g-C3N4 and the fast recombination rate of photogenerated electrons and holes, its photocatalytic performance is not high. In order to improve the photocatalytic performance of g-C3N4, g-C3N4 and Ti3C2T x MXene co-catalyst composite is an effective way to improve its photocatalytic efficiency. Similar to graphene, Ti3C2T x MXene sheets are also prone to self-stacking, which causes them to lose a large number of active sites available for reactions and reduces ion transport channels.

[0004] Therefore, it is necessary to improve the existing technology to provide a more reliable solution. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a CNT@Ti3C2T x MXene-coupled porous g-C3N4 photocatalyst, its preparation method and application. g-C3N4 was prepared by a one-step calcination method, and g-C3N4 with good dispersion and large porosity was obtained by thermal stripping. The protonated g-C3N4 was then bonded to the negatively charged CNT@Ti3C2T by electrostatic self-assembly. x MXene nanosheets are coupled to form heterostructures. Among them, one-dimensional CNT can effectively confine Ti3C2T x Self-stacking of MXene and the pore structure of g-C3N4 and Ti3C2T x The close connection between MXene sheets endows it with efficient photocatalytic response characteristics.

[0006] In order to solve the above technical problems, the technical solution adopted by the present invention is: in the first aspect of the present invention, a CNT@Ti3C2T x The preparation method of MXene coupled porous g-C3N4 photocatalyst comprises the following steps:

[0007] S1. Preparation of porous g-C3N4;

[0008] S2. Preparation of Ti3C2T x MXene nanosheet solution:

[0009] Lithium fluoride was added to hydrochloric acid, stirred, and then Ti3AlC2 powder was added to react under heating. After the reaction was completed, the precipitate was centrifuged and washed with deionized water until neutral to obtain Ti3C2T x MXene nanosheet solution;

[0010] S3. Preparation of CNT@Ti3C2T x MXene co-catalyst:

[0011] S3-1, dissolving sodium taurodeoxycholate hydrate in deionized water, then adding multi-walled carbon nanotubes, dispersing by ultrasonication, and stirring to obtain a multi-walled carbon nanotube dispersion;

[0012] S3-2, take the Ti3C2T prepared in step S2 x The MXene nanosheet solution was added to the multi-walled carbon nanotube dispersion, and then stirred for reaction after ultrasonic dispersion. After the reaction, the product was freeze-dried to obtain CNT@Ti3C2T x MXene co-catalyst;

[0013] S4. Preparation of CNT@Ti3C2T xMXene coupled porous g-C3N4 photocatalyst:

[0014] S4-1, protonating the porous g-C3N4 prepared in step S1 to obtain protonated porous g-C3N4;

[0015] S4-2, add the protonated porous g-C3N4 into deionized water, disperse it by ultrasonic, and then add the CNT@Ti3C2T prepared in step S3 x MXene co-catalyst, after ultrasonic dispersion, reacted under stirring, and after the reaction, the product was freeze-dried to obtain CNT@Ti3C2T x MXene-coupled porous g-C3N4 photocatalyst.

[0016] Preferably, step S1 specifically includes:

[0017] S1-1, using urea and melamine as raw materials, preparing a g-C3N4 precursor by calcination;

[0018] S1-1. Calcine the g-C3N4 precursor again in an air atmosphere to prepare porous g-C3N4.

[0019] Preferably, step S1 specifically includes:

[0020] S1-1, mix 10-40g urea and 1-4g melamine and grind them evenly, transfer them to a sealed alumina corundum crucible, and heat them at 2-10℃min -1 The temperature was raised to 500-600°C at a heating rate of 1.50°C, calcined for 2-8 hours, cooled to room temperature, and the product was ground to obtain a g-C3N4 precursor;

[0021] S1-1, the g-C3N4 precursor was heated at 2-10℃min -1 The temperature was raised to 550-600 °C at a heating rate, calcined again in an air atmosphere for 1-4 h, and cooled to room temperature to obtain porous g-C3N4.

[0022] Preferably, step S2 specifically includes:

[0023] 0.5-2g lithium fluoride is added to 15-20mL hydrochloric acid with a concentration of 12mol / L, stirred for 2-10min, then 0.5-2g Ti3AlC2 powder is added, reacted at 50-60℃ for 12-36h, centrifuged after the reaction, and the precipitate is washed with deionized water to neutrality to obtain Ti3C2T x MXene nanosheet solution.

[0024] Preferably, step S3 specifically includes:

[0025] S3-1, dissolving 180-720 mg of sodium taurodeoxycholate hydrate in 9.8-39.2 mL of deionized water, then adding 20-80 mg of multi-walled carbon nanotubes, ultrasonically dispersing for 5-30 min, and stirring for 2.5-10 h to obtain a multi-walled carbon nanotube dispersion;

[0026] S3-2, take the Ti3C2T prepared in step S2 x The MXene nanosheet solution was added to the multi-walled carbon nanotube dispersion, and the mixture was ultrasonically dispersed for 10-40 min and stirred for reaction for 1.5-6 h. After the reaction, the product was freeze-dried to obtain CNT@Ti3C2T x MXene co-catalyst;

[0027] Among them, Ti3C2T x Ti3C2T in MXene nanosheet solution x The mass ratio of MXene nanosheets to multi-walled carbon nanotubes in the multi-walled carbon nanotube dispersion is 0.5-2:1.5-6.

[0028] Preferably, in step S3-2, Ti3C2T x Ti3C2T in MXene nanosheet solution x The mass ratio of MXene nanosheets to multi-walled carbon nanotubes in the multi-walled carbon nanotube dispersion is 1:3.

[0029] Preferably, step S4 specifically includes:

[0030] S4-1, take 0.5-2g of the porous g-C3N4 prepared in step S1, add it to 75-300mL of 0.5-2mol / L HCl solution, ultrasonically treat for 1-4h, stir for 2-8h, wash the product with deionized water until neutral, freeze-dry, and obtain protonated porous g-C3N4;

[0031] S4-2, take 50-200 mg of protonated porous g-C3N4 and add it to 25-100 mL of deionized water, ultrasonically disperse it for 0.5-2 h, and then add the CNT@Ti3C2T prepared in step S3. x MXene co-catalyst, ultrasonic dispersion for 15-60 min, stirred reaction for 1-4 h, after the reaction, the product was freeze-dried to obtain CNT@Ti3C2T x MXene-coupled porous g-C3N4 photocatalyst.

[0032] Preferably, in step S4-2, CNT@Ti3C2T x The mass ratio of MXene to porous g-C3N4 is 1:100-3:100.

[0033] The second aspect of the present invention provides a CNT@Ti3C2T x MXene-coupled porous g-C3N4 photocatalyst, which was prepared by the method described above.

[0034] The third aspect of the present invention provides a CNT@Ti3C2T x Application of MXene-coupled porous g-C3N4 photocatalyst in photocatalytic degradation of organic pollutants.

[0035] The beneficial effects of the present invention are:

[0036] The present invention prepares g-C3N4 by a one-step calcination method, and obtains g-C3N4 with good dispersion and large porosity by thermal stripping; and then the protonated porous g-C3N4 is combined with negatively charged CNT@Ti3C2T by an electrostatic self-assembly method. x MXene nanosheets are coupled to form a heterostructure, and a photocatalyst that can efficiently degrade organic matter under visible light conditions is obtained; the preparation process of the present invention adopts an environmentally friendly and safe pyrolysis method, and the operation is simple and suitable for large-scale production, and has good application prospects in the fields of sewage treatment, waste gas treatment, etc.

[0037] Carbon nanotubes (CNTs) have a 1D tubular structure, high conductivity and high aspect ratio, which helps to form a conductive network structure; the present invention combines multi-walled carbon nanotubes with Ti3C2T x MXene is also used as a co-catalyst to combine with porous g-C3N4 to construct a composite photocatalyst. x The high conductivity of MXene and the inhibitory effect of CNT on its self-stacking enhance the ability of photogenerated electron transmission, reduce the recombination rate of photogenerated electrons and holes, and can significantly enhance the visible light catalytic effect of the catalyst. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 Shown is a flow chart of the preparation of the products of Examples 1-4 and Comparative Example 1 of the present invention;

[0039] Figure 2 Shown are XRD patterns of the products of the embodiments of the present invention and the comparative examples;

[0040] Figure 3 Shown are scanning electron microscope (SEM) images of the products of the embodiments of the present invention and the comparative examples;

[0041] Figure 4 Shown are ultraviolet-visible (UV-vis) absorption spectra of the embodiments of the present invention and the comparative examples;

[0042] Figure 5The graph shown is a graph showing the concentration variation of the photocatalysts prepared in Comparative Example 1, Example 1 and Comparative Example 4 when degrading the dye Rhodamine B under irradiation of a xenon lamp;

[0043] Figure 6 The graph shows the concentration change of the degradation dye rhodamine in the products of the embodiment of the present invention and the comparative example 1 under irradiation of a 300W xenon lamp;

[0044] Figure 7 The graph shown is a graph showing the concentration variation of the photocatalysts prepared in Comparative Example 1 and Comparative Examples 2-3 when degrading the dye Rhodamine B under xenon lamp irradiation;

[0045] Figure 8 Shown is a graph showing the concentration variation of the photocatalysts prepared in Comparative Example 3 and Example 3 when degrading the dye Rhodamine B under xenon lamp irradiation. DETAILED DESCRIPTION

[0046] The present invention is further described in detail below in conjunction with embodiments so that those skilled in the art can implement the invention with reference to the description.

[0047] It should be understood that terms such as “having”, “including” and “comprising” used herein do not exclude the existence or addition of one or more other elements or combinations thereof.

[0048] The test methods used in the following examples are conventional methods unless otherwise specified. The materials and reagents used in the following examples are all commercially available unless otherwise specified. In the following examples, if no specific conditions are specified, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, if the manufacturer is not specified, are all conventional products that can be purchased commercially.

[0049] The present invention provides a CNT@Ti3C2T x MXene coupled porous g-C3N4 photocatalyst, the preparation method thereof comprises the following steps:

[0050] S1. Preparation of porous g-C3N4 by two-step calcination method:

[0051] S1-1, mix 10-40g urea and 1-4g melamine and grind them evenly, transfer them to a sealed alumina corundum crucible, and heat them at 2-10℃min -1 The temperature was raised to 500-600°C at a heating rate of 1000 ℃, calcined for 2-8 hours, cooled to room temperature, and the blocky g-C3N4 product was ground to obtain a g-C3N4 precursor;

[0052] S1-1, the g-C3N4 precursor was heated at 2-10℃min -1The temperature was raised to 550-600 °C at a heating rate, calcined again in an air atmosphere for 1-4 h, and cooled to room temperature to obtain porous g-C3N4.

[0053] S2. Preparation of Ti3C2T x MXene nanosheet solution:

[0054] The present invention selectively etches the Al atomic layer from the Ti3AlC2 MAX phase to prepare Ti3C2T x MXene; the specific preparation method is:

[0055] 0.5-2g lithium fluoride is added to 15-20mL hydrochloric acid with a concentration of 12mol / L, stirred for 2-10min, then 0.5-2g Ti3AlC2 powder is added, reacted at 50-60℃ for 12-36h, centrifuged after the reaction, and the precipitate is washed with deionized water to neutrality to obtain Ti3C2T x MXene nanosheet solution.

[0056] S3. Preparation of CNT@Ti3C2T x MXene co-catalyst:

[0057] S3-1, dissolving 180-720 mg of sodium taurodeoxycholate hydrate (STDOC) in 9.8-39.2 mL of deionized water, then adding 20-80 mg of multi-walled carbon nanotubes (MWCNT), ultrasonically dispersing for 5-30 min, and stirring for 2.5-10 h to obtain a multi-walled carbon nanotube dispersion;

[0058] S3-2, take the Ti3C2T prepared in step S2 x The MXene nanosheet solution was added to the multi-walled carbon nanotube dispersion, and the mixture was ultrasonically dispersed for 10-40 min and stirred for reaction for 1.5-6 h. After the reaction, the product was freeze-dried to obtain CNT@Ti3C2T x MXene co-catalyst;

[0059] Among them, Ti3C2T x Ti3C2T in MXene nanosheet solution x The mass ratio of MXene nanosheets to multi-walled carbon nanotubes in the multi-walled carbon nanotube dispersion is 0.5-2:1.5-6.

[0060] S4. Preparation of CNT@Ti3C2T x MXene coupled porous g-C3N4 photocatalyst:

[0061] S4-1, take 0.5-2g of the porous g-C3N4 prepared in step S1, add it to 75-300mL of 0.5-2mol / L HCl solution, ultrasonically treat for 1-4h, stir for 2-8h, wash the product with deionized water until neutral, freeze-dry, and obtain protonated porous g-C3N4;

[0062] S4-2, take 50-200 mg of protonated porous g-C3N4 and add it to 25-100 mL of deionized water, ultrasonically disperse it for 0.5-2 h, and then add the CNT@Ti3C2T prepared in step S3. x MXene co-catalyst, ultrasonic dispersion for 15-60 min, stirred reaction for 1-4 h, after the reaction, the product was freeze-dried to obtain CNT@Ti3C2T x MXene-coupled porous g-C3N4 photocatalyst.

[0063] In a preferred embodiment, in step S3-2, Ti3C2T x Ti3C2T in MXene nanosheet solution x The mass ratio of MXene nanosheets to multi-walled carbon nanotubes in the multi-walled carbon nanotube dispersion is 1:3.

[0064] In a preferred embodiment, in step S4-2, CNT@Ti3C2T x The mass ratio of MXene to porous g-C3N4 is 1:100-3:100.

[0065] The present invention also provides a CNT@Ti3C2T x Application of MXene-coupled porous g-C3N4 photocatalyst in photocatalytic degradation of organic pollutants.

[0066] The photocatalyst provided by the present invention has the characteristics of preparing g-C3N4 by a one-step calcination method, and obtaining g-C3N4 with good dispersion and large porosity by thermal stripping.

[0067] The photocatalyst provided by the present invention also has the characteristics of combining the protonated porous g-C3N4 with the negatively charged CNT@Ti3C2T by electrostatic self-assembly. x MXene nanosheets are coupled to form heterostructures.

[0068] The photocatalyst provided by the present invention also has the characteristic that the one-dimensional CNT can effectively limit the Ti3C2T x Self-stacking of MXene and the pore structure of g-C3N4 and Ti3C2T x The close connection between MXene sheets endows it with efficient photocatalytic response characteristics.

[0069] The photocatalyst provided by the present invention also has novel structure, excellent performance, and excellent visible light catalytic effect. It can degrade organic matter under visible light, has the characteristics of high efficiency, energy saving, and environmental protection, and has good application prospects in the fields of sewage treatment, waste gas treatment, etc.

[0070] The above is the overall concept of the present invention, and detailed embodiments and comparative examples are provided below on the basis of the overall concept of the present invention to further illustrate the present invention.

[0071] The main materials and experimental instruments involved in the following examples and comparative examples are shown in Tables 1 and 2, respectively.

[0072] Table 1

[0073]

[0074] Table 2

[0075]

[0076]

[0077] Example 1

[0078] A porous g-C3N4, the preparation method of which comprises the following steps:

[0079] S1. Grind 20 g urea and 2 g melamine in a mortar and transfer them to a 100 mL sealed alumina corundum crucible. In a tube furnace (air atmosphere) at 550 °C for 5 min. -1 The calcination was carried out at a heating rate of 4 h; then, after cooling to room temperature, the crucible was taken out to obtain a bulk g-C3N4 precursor, and the bulk g-C3N4 precursor was ground with a grinding rod until there were no obvious particles;

[0080] S2, the product of step S1 is placed in a tube furnace (air atmosphere) at 5°C min -1 The resulting composite was calcined at 550 °C for 2 h at a heating rate of 1.5 % and finally cooled to room temperature to obtain porous g-C3N4.

[0081] Example 2

[0082] A CNT@Ti3C2T x MXene coupled porous g-C3N4 photocatalyst, the preparation method thereof comprises the following steps:

[0083] S1. Preparation of porous g-C3N4 by two-step calcination method:

[0084] S1-1. Grind 20 g urea and 2 g melamine in a mortar and transfer them to a 100 mL sealed alumina corundum crucible. In a tube furnace (air atmosphere) at 550 °C for 5 min. -1 The calcination was carried out at a heating rate of 4 h; then, after cooling to room temperature, the crucible was taken out to obtain a bulk g-C3N4 precursor, and the bulk g-C3N4 precursor was ground using a grinding rod until there were no obvious particles.

[0085] S1-2, the product of step S1-1 was placed in a tube furnace (air atmosphere) at 5°C min -1 The sample was calcined at 550 °C for 2 h at a heating rate of 1.5 ℃ and then cooled to room temperature to obtain porous g-C3N4.

[0086] S2. Preparation of Ti3C2T x MXene nanosheet solution:

[0087] 1 g of lithium fluoride (LiF) was added to 20 mL of 12 mol / L hydrochloric acid (HCl) and stirred for 5 min. 1 g of Ti3AlC2 powder was slowly added to the above solution and reacted at 55 °C for 21 h. After the reaction, the precipitate was centrifuged and washed with deionized water until neutral to obtain Ti3C2T x MXene nanosheet solution.

[0088] S3. Preparation of CNT@Ti3C2T x MXene co-catalyst:

[0089] S3-1, adding 360 mg of sodium taurodeoxycholate hydrate (STDOC) to 19.6 mL of water and stirring to dissolve, then slowly adding 40 mg of MWCNT (multi-walled carbon nanotube) thereto, ultrasonicating for 15 min, and then stirring for 5 h to obtain a multi-walled carbon nanotube dispersion;

[0090] S3-2, according to Ti3C2T x MXene:MWCNT = 1:3 ratio, 13.33 mg Ti3C2T was added to the multi-walled carbon nanotube dispersion x MXene, ultrasonic for 20 min, and then stirred for 3 h; after the reaction, the product was freeze-dried to obtain CNT@Ti3C2T x MXene co-catalyst;

[0091] S4. Preparation of CNT@Ti3C2T x MXene coupled porous g-C3N4 photocatalyst:

[0092] S4-1, 1 g of porous g-C3N4 was added to 150 mL of HCl solution (concentration 1 mol / L), ultrasonically treated for 2 h, and stirred for 4 h; then the sample was repeatedly washed with deionized water until the pH value of the aqueous dispersion of the last washing was close to 7; then it was freeze-dried to obtain protonated porous g-C3N4;

[0093] S4-2, 100 mg of protonated porous g-C3N4 was added to 50 mL of H2O and ultrasonicated for 1 h; then 1 mg of CNT@Ti3C2T x MXene, then ultrasonicated for 30 min, stirred for 2 h, and after the reaction, the product was freeze-dried to obtain CNT@Ti3C2T x MXene-coupled porous g-C3N4 photocatalyst.

[0094] Example 3

[0095] A CNT@Ti3C2T x MXene coupled porous g-C3N4 photocatalyst, the preparation method thereof comprises the following steps:

[0096] S1. Preparation of porous g-C3N4 by two-step calcination method:

[0097] S1-1. Grind 20 g urea and 2 g melamine in a mortar and transfer them to a 100 mL sealed alumina corundum crucible. In a tube furnace (air atmosphere) at 550 °C for 5 min. -1 The calcination was carried out at a heating rate of 4 h; then, after cooling to room temperature, the crucible was taken out to obtain a bulk g-C3N4 precursor, and the bulk g-C3N4 precursor was ground with a grinding rod until there were no obvious particles;

[0098] S1-2, the product of step S1-1 was placed in a tube furnace (air atmosphere) at 5°C min -1 The sample was calcined at 550 °C for 2 h at a heating rate of 1.5 ℃ and then cooled to room temperature to obtain porous g-C3N4.

[0099] S2. Preparation of Ti3C2T x MXene nanosheet solution:

[0100] 1 g of lithium fluoride (LiF) was added to 20 mL of 12 mol / L hydrochloric acid (HCl) and stirred for 5 min. 1 g of Ti3AlC2 powder was slowly added to the above solution and reacted at 55 °C for 21 h. After the reaction, the precipitate was centrifuged and washed with deionized water until neutral to obtain Ti3C2T x MXene nanosheet solution.

[0101] S3. Preparation of CNT@Ti3C2T x MXene co-catalyst:

[0102] S3-1, adding 360 mg of sodium taurodeoxycholate hydrate (STDOC) to 19.6 mL of water and stirring to dissolve, then slowly adding 40 mg of MWCNT (multi-walled carbon nanotube) thereto, ultrasonicating for 15 min, and then stirring for 5 h to obtain a multi-walled carbon nanotube dispersion;

[0103] S3-2, according to Ti3C2T x MXene:MWCNT = 1:3 ratio, 13.33 mg Ti3C2T was added to the multi-walled carbon nanotube dispersion x MXene, ultrasonic for 20 min, and then stirred for 3 h; after the reaction, the product was freeze-dried to obtain CNT@Ti3C2T x MXene co-catalyst;

[0104] S4. Preparation of CNT@Ti3C2T x MXene coupled porous g-C3N4 photocatalyst:

[0105] S4-1, 1 g of porous g-C3N4 was added to 150 mL of HCl solution (concentration 1 mol / L), ultrasonically treated for 2 h, and stirred for 4 h; then the sample was repeatedly washed with deionized water until the pH value of the aqueous dispersion of the last washing was close to 7; then it was freeze-dried to obtain protonated porous g-C3N4;

[0106] S4-2, 100 mg of protonated porous g-C3N4 was added to 50 mL of H2O and ultrasonicated for 1 h; then 2 mg of CNT@Ti3C2T x MXene, then ultrasonicated for 30 min, stirred for 2 h, and after the reaction, the product was freeze-dried to obtain CNT@Ti3C2T x MXene-coupled porous g-C3N4 photocatalyst.

[0107] Example 4

[0108] A CNT@Ti3C2T x MXene coupled porous g-C3N4 photocatalyst, the preparation method thereof comprises the following steps:

[0109] S1. Preparation of porous g-C3N4 by two-step calcination method:

[0110] S1-1. Grind 20 g urea and 2 g melamine in a mortar and transfer them to a 100 mL sealed alumina corundum crucible. In a tube furnace (air atmosphere) at 550 °C for 5 min.-1 The calcination was carried out at a heating rate of 4 h; then, after cooling to room temperature, the crucible was taken out to obtain a bulk g-C3N4 precursor, and the bulk g-C3N4 precursor was ground with a grinding rod until there were no obvious particles;

[0111] S1-2, the product of step S1-1 was placed in a tube furnace (air atmosphere) at 5°C min -1 The sample was calcined at 550 °C for 2 h at a heating rate of 1.5 ℃ and then cooled to room temperature to obtain porous g-C3N4.

[0112] S2. Preparation of Ti3C2T x MXene nanosheet solution:

[0113] 1 g of lithium fluoride (LiF) was added to 20 mL of 12 mol / L hydrochloric acid (HCl) and stirred for 5 min. 1 g of Ti3AlC2 powder was slowly added to the above solution and reacted at 55 °C for 21 h. After the reaction, the precipitate was centrifuged and washed with deionized water until neutral to obtain Ti3C2T x MXene nanosheet solution.

[0114] S3. Preparation of CNT@Ti3C2T x MXene co-catalyst:

[0115] S3-1, adding 360 mg of sodium taurodeoxycholate hydrate (STDOC) to 19.6 mL of water and stirring to dissolve, then slowly adding 40 mg of MWCNT (multi-walled carbon nanotube) thereto, ultrasonicating for 15 min, and then stirring for 5 h to obtain a multi-walled carbon nanotube dispersion;

[0116] S3-2, according to Ti3C2T x MXene:MWCNT = 1:3 ratio, 13.33 mg Ti3C2T was added to the multi-walled carbon nanotube dispersion x MXene, ultrasonic for 20 min, and then stirred for 3 h; after the reaction, the product was freeze-dried to obtain CNT@Ti3C2T x MXene co-catalyst;

[0117] S4. Preparation of CNT@Ti3C2T x MXene coupled porous g-C3N4 photocatalyst:

[0118] S4-1, 1 g of porous g-C3N4 was added to 150 mL of HCl solution (concentration 1 mol / L), ultrasonically treated for 2 h, and stirred for 4 h; then the sample was repeatedly washed with deionized water until the pH value of the aqueous dispersion of the last washing was close to 7; then it was freeze-dried to obtain protonated porous g-C3N4;

[0119] S4-2, 100 mg of protonated porous g-C3N4 was added to 50 mL of H2O and ultrasonicated for 1 h; then 3 mg of CNT@Ti3C2T x MXene, then ultrasonicated for 30 min, stirred for 2 h, and after the reaction, the product was freeze-dried to obtain CNT@Ti3C2T x MXene-coupled porous g-C3N4 photocatalyst.

[0120] Comparative Example 1

[0121] A bulk g-C3N4 precursor, the preparation method of which comprises the following steps:

[0122] 20 g of urea and 2 g of melamine were ground evenly in a mortar and then transferred to a 100 mL sealed alumina corundum crucible and heated in a tube furnace (air atmosphere) at 550 °C for 5 min. -1 The calcination was carried out at a heating rate of 4 h; then, after cooling to room temperature, the crucible was taken out to obtain a bulk g-C3N4 precursor, and the bulk g-C3N4 precursor was ground using a grinding rod until there were no obvious particles.

[0123] Comparative Example 2

[0124] A Ti3C2T x MXene coupled bulk g-C3N4 photocatalyst, the preparation method thereof comprises the following steps:

[0125] S1. Grind 20 g urea and 2 g melamine in a mortar and transfer them to a 100 mL sealed alumina corundum crucible. In a tube furnace (air atmosphere) at 550 °C for 5 min. -1 The calcination was carried out at a heating rate of 4 h; then, after cooling to room temperature, the crucible was taken out to obtain a bulk g-C3N4 precursor, and the bulk g-C3N4 precursor was ground with a grinding rod until there were no obvious particles;

[0126] S2. Preparation of Ti3C2T x MXene nanosheet solution:

[0127] 1 g of lithium fluoride (LiF) was added to 20 mL of 12 mol / L hydrochloric acid (HCl) and stirred for 5 min. 1 g of Ti3AlC2 powder was slowly added to the above solution and reacted at 55 °C for 21 h. After the reaction, the precipitate was centrifuged and washed with deionized water until neutral to obtain Ti3C2T x MXene nanosheet solution.

[0128] S3、Ti3C2T xPreparation of MXene-coupled bulk g-C3N4 photocatalyst

[0129] S3-1, add 1g of bulk g-C3N4 into 150mL of HCl solution (concentration 1mol / L), ultrasonicate for 2h, and stir for 4h; then wash the sample repeatedly with deionized water until the pH value of the aqueous dispersion of the last washing is close to 7; then freeze-dry it to obtain protonated bulk g-C3N4;

[0130] S3-2, 100 mg of protonated bulk g-C3N4 was added to 50 mL of H2O and ultrasonicated for 1 h; then 2 mg of Ti3C2T x MXene, then ultrasonicated for 30 min, stirred for 2 h, and the product was freeze-dried after the reaction to obtain Ti3C2T x MXene-coupled bulk g-C3N4 photocatalyst.

[0131] Comparative Example 3

[0132] A CNT@Ti3C2T x MXene coupled bulk g-C3N4 photocatalyst, the preparation method thereof comprises the following steps:

[0133] S1. Grind 20 g urea and 2 g melamine in a mortar and transfer them to a 100 mL sealed alumina corundum crucible. In a tube furnace (air atmosphere) at 550 °C for 5 min. -1 The calcination was carried out at a heating rate of 4 h; then, after cooling to room temperature, the crucible was taken out to obtain a bulk g-C3N4 precursor, and the bulk g-C3N4 precursor was ground with a grinding rod until there were no obvious particles;

[0134] S2. Preparation of Ti3C2T x MXene nanosheet solution:

[0135] 1 g of lithium fluoride (LiF) was added to 20 mL of 12 mol / L hydrochloric acid (HCl) and stirred for 5 min. 1 g of Ti3AlC2 powder was slowly added to the above solution and reacted at 55 °C for 21 h. After the reaction, the precipitate was centrifuged and washed with deionized water until neutral to obtain Ti3C2T x MXene nanosheet solution.

[0136] S3. Preparation of CNT@Ti3C2T x MXene co-catalyst:

[0137] S3-1, adding 360 mg of sodium taurodeoxycholate hydrate (STDOC) to 19.6 mL of water and stirring to dissolve, then slowly adding 40 mg of MWCNT (multi-walled carbon nanotube) thereto, ultrasonicating for 15 min, and then stirring for 5 h to obtain a multi-walled carbon nanotube dispersion;

[0138] S3-2, according to Ti3C2T x MXene:MWCNT = 1:3 ratio, 13.33 mg Ti3C2T was added to the multi-walled carbon nanotube dispersion x MXene, ultrasonic for 20 min, and then stirred for 3 h; after the reaction, the product was freeze-dried to obtain CNT@Ti3C2T x MXene co-catalyst;

[0139] S4. Preparation of CNT@Ti3C2T x MXene-coupled bulk g-C3N4 photocatalyst:

[0140] S4-1, 1g of block g-C3N4 was added to 150mL of HCl solution (concentration 1mol / L), ultrasonically treated for 2h, and stirred for 4h; then the sample was repeatedly washed with deionized water until the pH value of the aqueous dispersion of the last washing was close to 7; then it was freeze-dried to obtain protonated block g-C3N4;

[0141] S4-2, 100 mg of protonated bulk g-C3N4 was added to 50 mL of H2O and ultrasonicated for 1 h; then 2 mg of CNT@Ti3C2T x MXene, then ultrasonicated for 30 min, stirred for 2 h, and after the reaction, the product was freeze-dried to obtain CNT@Ti3C2T x MXene-coupled bulk g-C3N4 photocatalyst.

[0142] Comparative Example 4

[0143] A conventional bulk g-C3N4 precursor, the preparation method of which comprises the following steps:

[0144] 6 g of melamine was weighed in a mortar and then transferred to a 100 mL sealed alumina corundum crucible. The crucible was heated at 550 °C in a tube furnace (air atmosphere) at 5 °C min -1 The calcination was carried out at a heating rate of 4 h; then, after cooling to room temperature, the crucible was taken out to obtain a bulk g-C3N4 precursor, and the bulk g-C3N4 precursor was ground using a grinding rod until there were no obvious particles.

[0145] Performance Characterization and Testing

[0146] (1) XRD characterization

[0147] The crystal structures of the photocatalysts of Comparative Example 1 and Examples 1-4 were obtained by XRD testing. Figure 2 Comparative Example 1 and Examples 1-4 present two diffraction peaks at 13.0° and 27.3°, respectively, which are attributed to the planar arrangement (100) plane of the repeating tri-s-triazine unit and the stacking (002) plane of the oriented aromatic structure.

[0148] (2) SEM morphology characterization

[0149] Figure 3 Shown are surface scanning electron microscope (SEM) images of the photocatalysts of Comparative Example 1 and Examples 1-4. Figure 3 (a) is the SEM image of the bulk g-C3N4 precursor of Comparative Example 1, which shows that Comparative Example 1 is composed of bulk carbon nitride, has a layered structure and has trace pores.

[0150] Figure 3 (b) is the SEM image of the porous g-C3N4 of Example 1, which shows that after the bulk g-C3N4 precursor is thermally stripped at high temperature, the surface pores increase and the carbon nitride accumulation decreases. Larger pores and loose accumulation can provide more active sites, which helps to improve the photocatalytic efficiency.

[0151] Figure 3 (c) is the CNT@Ti3C2T in Example 2 x SEM image of MXene, from which it can be seen that carbon nanotubes are adsorbed on Ti3C2T x The surface of MXene nanosheets is evenly distributed. The one-dimensional structure of carbon nanotubes is similar to that of Ti3C2T x The two-dimensional structure of MXene nanosheets is perfectly combined with Ti3C2T x MXene nanosheets have the property of self-stacking, which affects Ti3C2T x The performance of MXene and the introduction of carbon nanotubes improve this problem.

[0152] Figure 3 (d, e, f) are CNT@Ti3C2T in Example 3 x SEM image of MXene-coupled porous g-C3N4 photocatalyst. The protonated porous g-C3N4 can interact with the negatively charged Ti3C2T x The nanosheets form a close interface connection.

[0153] (3) Ultraviolet-visible (UV-vis) absorption spectrum

[0154] Figure 4The UV-vis absorption spectra of Comparative Example 1 and Examples 1-4 are shown, which show the absorption range of the samples in the visible light region. The light absorption edge of Comparative Example 1 is at a wavelength of 456nm. After thermal stripping, the light absorption intensity of the sample of Example 1 increased. From the tangent line of the absorption inflection point, it is known that the absorption edge increased to 463nm; this is because the thermal stripping caused the aperture of Example 1 to increase, which can absorb more light, resulting in a red shift in its absorption range. When CNT@Ti3C2T x The overall absorbance of the photocatalysts obtained by coupling MXene with Example 1 (Examples 2, 3, and 4) is further improved, and the absorption edge further shows a red shift, with the absorption range reaching 475 nm (Example 3). x The full-spectrum absorption characteristics of MXene can make full use of the visible light band, thereby improving the utilization rate of sunlight and thus improving its photocatalytic performance.

[0155] (4) Experimental verification of photocatalytic degradation of dye (Rhodamine B) in water by photocatalyst

[0156] Experimental method: RhB was used as the research object to investigate its photocatalytic activity. A certain amount of photocatalyst was added to 100 mL of RhB solution and stirred for 30 min in the dark to achieve adsorption-desorption equilibrium. Then, the photocatalytic degradation effect of RhB was studied under a 300W xenon lamp with λ>420nm. The general method is as follows:

[0157] (1) 30 mg of photocatalyst was added to 100 ml of rhodamine solution (20 mg / ml) in the dark for 30 min to reach adsorption-desorption equilibrium.

[0158] (2) During the illumination process, 3 ml of sample was collected every 15 minutes and the absorbance of the sample was measured by UV-visible spectrophotometer.

[0159] (3) Calculate the degradation rate of rhodamine B (%) based on the intensity change of the 550nm absorption peak in the measured solution absorption spectrum = 1-C t / C0=1-A t / A0. Where C0 and A0 are the initial concentration of rhodamine B in water and its absorbance at 550nm before illumination, C t and A t It is the concentration of Rhodamine B in water after a certain period of illumination and its absorbance at 550nm.

[0160] Figure 5 The graph shows the concentration change of the photocatalysts prepared in comparative example 1, embodiment 1 and comparative example 4 under xenon lamp irradiation, which degrade the dye rhodamine B. Figure 5It can be seen that the degradation effect of RhB by the sample of Example 4 obtained by calcining with melamine alone is very poor, and the degradation effect of the sample of Example 1 obtained by calcining with urea is improved, which indicates that the addition of urea introduces nitrogen doping and improves the catalytic effect. After thermal stripping of Example 1, the increase of its pores leads to an enhanced light absorption capacity, which further improves the catalytic effect of Example 1.

[0161] Figure 6 The graph shows the concentration change of the photocatalysts prepared in Comparative Example 1 and Examples 1-4 under xenon lamp irradiation to degrade the dye Rhodamine B. Figure 6 It can be seen that after stirring for 15 minutes in the dark, the sample is close to the absorption-desorption equilibrium. The degradation effect of comparative example 1 on RhB can reach 40%. After further calcination, example 1 can degrade 57% of RhB within 45 minutes. x After the MXene mixture, 94% of RhB was degraded within 45 min during the illumination process in Example 3. This is mainly due to the degradation of Ti3C2T x The high conductivity of MXene and the suppression of its self-stacking by CNTs, therefore, facilitate the transfer of photoexcited electrons.

[0162] Figure 7 The graph shows the concentration change of the photocatalyst prepared in Comparative Example 1 and Comparative Examples 2-3 under xenon lamp irradiation, which degrades the dye Rhodamine B. Figure 6 As can be seen, adding a single Ti3C2T x The catalytic effect of MXene is improved compared with bulk g-C3N4, but it is not as good as CNT@Ti3C2T x There is still a gap compared with MXene, which may be due to Ti3C2T x MXene self-stacking causes.

[0163] Figure 8 The graph shows the concentration change of the photocatalyst prepared in comparative example 3 and example 3 under xenon lamp irradiation to degrade the dye rhodamine B. Figure 8 It can be seen that the photocatalytic effect of Example 3 is improved by nearly 10% compared with that of Comparative Example 3, which also shows that compared with bulk g-C3N4, the formation of porous g-C3N4 improves the catalytic effect.

[0164] The bulk carbon nitride of the present invention is prepared by calcining a mixture of melamine and urea. Unlike the conventional solution of calcining urea (such as Comparative Example 4), melamine is used as a carbon nitride carrier in the present invention, and the introduction of urea brings about the release of a large amount of ammonia, which can form a porous structure and introduce nitrogen doping, thereby improving its photocatalytic ability. After high-temperature thermal stripping, the bulk carbon nitride has more and larger surface pores, and the accumulation of carbon nitride is reduced. The porous carbon nitride formed can provide more active sites, which helps to improve the photocatalytic efficiency.

[0165] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes. They can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to specific details.

Claims

1. A CNT@Ti3C2T x The method for preparing MXene-coupled porous g-C3N4 photocatalyst is characterized in that: The following steps are involved: S1, preparation of porous g-C3N4; S2. Preparation of Ti3C2T x MXene nanosheet solution: Lithium fluoride was added to hydrochloric acid, stirred, and then Ti3AlC2 powder was added to react under heating. After the reaction was completed, the precipitate was centrifuged and washed with deionized water until neutral to obtain Ti3C2T x MXene nanosheet solution; S3. Preparation of CNT@Ti3C2T x MXene co-catalyst: S3-1, dissolving sodium taurodeoxycholate hydrate in deionized water, then adding multi-walled carbon nanotubes, dispersing by ultrasonication, and stirring to obtain a multi-walled carbon nanotube dispersion; S3-2, take the Ti3C2T prepared in step S2 x The MXene nanosheet solution was added to the multi-walled carbon nanotube dispersion, and then stirred for reaction after ultrasonic dispersion. After the reaction, the product was freeze-dried to obtain CNT@Ti3C2T x MXene co-catalyst; S4. Preparation of CNT@Ti3C2T x MXene coupled porous g-C3N4 photocatalyst: S4-1, protonating the porous g-C3N4 prepared in step S1 to obtain protonated porous g-C3N4; S4-2, add the protonated porous g-C3N4 into deionized water, disperse it by ultrasonic, and then add the CNT@Ti3C2T prepared in step S3 x MXene co-catalyst, after ultrasonic dispersion, reacted under stirring, and after the reaction, the product was freeze-dried to obtain CNT@Ti3C2T x MXene-coupled porous g-C3N4 photocatalyst.

2. CNT@Ti3C2T according to claim 1 x The method for preparing MXene-coupled porous g-C3N4 photocatalyst is characterized in that: Step S1 specifically includes: S1-1, using urea and melamine as raw materials, preparing a g-C3N4 precursor by calcination; S1-1. Calcine the g-C3N4 precursor again in an air atmosphere to prepare porous g-C3N4.

3. CNT@Ti3C2T according to claim 2 x The method for preparing MXene-coupled porous g-C3N4 photocatalyst is characterized in that: Step S1 specifically includes: S1-1, mix 10-40g urea and 1-4g melamine and grind them evenly, transfer them to a sealed alumina corundum crucible, and heat them at 2-10℃min -1 The temperature was raised to 500-600°C at a heating rate of 1.50°C, calcined for 2-8 hours, cooled to room temperature, and the product was ground to obtain a g-C3N4 precursor; S1-1, the g-C3N4 precursor was heated at 2-10℃min -1 The temperature was raised to 550-600 °C at a heating rate, calcined again in an air atmosphere for 1-4 h, and cooled to room temperature to obtain porous g-C3N4.

4. CNT@Ti3C2T according to claim 1 x The method for preparing MXene-coupled porous g-C3N4 photocatalyst is characterized in that: Step S2 specifically includes: Add 0.5-2g lithium fluoride to 15-20mL 12mol / L hydrochloric acid, stir for 2-10min, then add 0.5-2g Ti3AlC2 powder, react at 50-60℃ for 12-36h, centrifuge after the reaction, wash the precipitate with deionized water until neutral, and obtain Ti3C2T x MXene nanosheet solution.

5. CNT@Ti3C2T according to claim 1 x The method for preparing MXene-coupled porous g-C3N4 photocatalyst is characterized in that: Step S3 specifically includes: S3-1, dissolving 180-720 mg of sodium taurodeoxycholate hydrate in 9.8-39.2 mL of deionized water, then adding 20-80 mg of multi-walled carbon nanotubes, ultrasonically dispersing for 5-30 min, and stirring for 2.5-10 h to obtain a multi-walled carbon nanotube dispersion; S3-2, take the Ti3C2T prepared in step S2 x The MXene nanosheet solution was added to the multi-walled carbon nanotube dispersion, and the mixture was stirred and reacted for 1.5-6 hours after ultrasonic dispersion for 10-40 minutes. After the reaction, the product was freeze-dried to obtain CNT@Ti3C2T x MXene co-catalyst; Among them, Ti3C2T x Ti3C2T in MXene nanosheet solution x The mass ratio of MXene nanosheets to multi-walled carbon nanotubes in the multi-walled carbon nanotube dispersion is 0.5-2:1.5-6.

6. CNT@Ti3C2T according to claim 5 x The method for preparing MXene-coupled porous g-C3N4 photocatalyst is characterized in that: In step S3-2, Ti3C2T x Ti3C2T in MXene nanosheet solution x The mass ratio of MXene nanosheets to multi-walled carbon nanotubes in the multi-walled carbon nanotube dispersion is 1:

3.

7. The CNT@Ti3C2T according to claim 1 x The method for preparing MXene-coupled porous g-C3N4 photocatalyst is characterized in that: Step S4 specifically includes: S4-1, take 0.5-2g of the porous g-C3N4 prepared in step S1, add it to 75-300mL of 0.5-2mol / L HCl solution, ultrasonically treat for 1-4h, stir for 2-8h, wash the product with deionized water until neutral, freeze-dry, and obtain protonated porous g-C3N4; S4-2, take 50-200 mg of protonated porous g-C3N4 and add it to 25-100 mL of deionized water, ultrasonically disperse it for 0.5-2 h, and then add the CNT@Ti3C2T prepared in step S3. x MXene co-catalyst, ultrasonic dispersion for 15-60 min, stirred reaction for 1-4 h, after the reaction, the product was freeze-dried to obtain CNT@Ti3C2T x MXene-coupled porous g-C3N4 photocatalyst.

8. The CNT@Ti3C2T according to claim 7 x The method for preparing MXene-coupled porous g-C3N4 photocatalyst is characterized in that: In step S4-2, CNT@Ti3C2T x The mass ratio of MXene to porous g-C3N4 is 1:100-3:

100.

9. A CNT@Ti3C2T x MXene coupled porous g-C3N4 photocatalyst, characterized by: It is prepared by the method according to any one of claims 1 to 8.

10. A CNT@Ti3C2T as claimed in claim 9 x Application of MXene-coupled porous g-C3N4 photocatalyst in photocatalytic degradation of organic pollutants.

Citation Information

Cited By

  • Catalyst for sunlight degradation of polyurethane adhesive as well as preparation method and application of catalyst

    CN120605757A

  • A catalyst, preparation method and application for solar-degradable polyurethane adhesives

    CN120605757B